1992
DOI: 10.1007/bf01245347
|View full text |Cite
|
Sign up to set email alerts
|

Typical and atypical neuroleptics antagonize MK-801-induced locomotion and stereotypy in rats

Abstract: The effects of typical and atypical neuroleptics on MK-801-induced locomotor activity and stereotyped sniffing were tested. Pretreatment with the typical neuroleptic haloperidol (0.01, 0.05, 0.1, 0.5 mg/kg SC) and the dopamine D2 receptor selective antagonist eticlopride (0.005, 0.01, 0.05 mg/kg SC) each resulted in significant and dose-dependent reductions of locomotor activity and sniffing. The atypical neuroleptic clozapine (1.0, 5.0, 10.0 mg/kg SC) was somewhat unique in that all doses reduced locomotor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
1
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 32 publications
10
35
1
1
Order By: Relevance
“…The observation that dizocilpine significantly decreased running times in the maze is also in line with studies showing a dizocilpine-induced increase of spontaneous locomotor activity (Tiedtke et al, 1990;Hoffman, 1992). Regarding the relationship between errors and corresponding running times, both measures seem to be independent regardless of the treatment used here: I) Dizocilpine-treated animals had the same running times in correct and incorrect choices.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The observation that dizocilpine significantly decreased running times in the maze is also in line with studies showing a dizocilpine-induced increase of spontaneous locomotor activity (Tiedtke et al, 1990;Hoffman, 1992). Regarding the relationship between errors and corresponding running times, both measures seem to be independent regardless of the treatment used here: I) Dizocilpine-treated animals had the same running times in correct and incorrect choices.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies showed that clozapine antagonized dizocilpine-induced stereotypy (Tiedtke etal., 1990;Hoffman, 1992). Furthermore, stereotypy induced by intrastriatal injection of AP-5 was antagonized by systemic administration of clozapine (Schmidt, 1986).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This idea is corroborated by the fact that chronic stress reduces basal release of dopamine; in addition, drugs with antidepressant action facilitate the dopaminergic transmission [48]. These results agree with behavioral studies suggesting that behavioral effects of NMDA antagonists are blocked by antipsychotic drugs [49,50]. The action of these drugs in this model made possible the blockade of the symptoms caused by acute administration of ketamine.…”
Section: Discussionsupporting
confidence: 79%
“…90,91 In addition, MK-801-induced locomotor activation can be blocked by typical and atypical antipsychotics. [92][93][94] However, certain behavioral responses induced by NMDA antagonists are differentially affected by atyptical drugs. For example, clozapine and olanzapine blocked PCP-induced deficits in social interactions, whereas haloperidol and risperidone were ineffective.…”
Section: Effects Of Typical and Atypical Drugs On Neurotoxicological mentioning
confidence: 99%